PRETREATMENT STRATEGIES FOR IMPROVED ASTAXANTHIN RECOVERY FROM CRAB CARAPACE WASTE: ENZYMATIC VS. STEAM-EXPLOSION METHODS - Retno Ayu Kurniasih; Sri Raharjo; Rachma Wikandari; Andriati Ningrum (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2026)
Crab meat pasteurization industries produce carapace waste containing astaxanthin. The carapace composition includes minerals, proteins, and chitin, which can hinder the astaxanthin extraction. This study investigated the effects of alcalase and steam-explosion pretreatments on the astaxanthin yield and antioxidant activity of astaxanthin extracted from the carapace powder. The alcalase pretreatment was determined using OVAT (One-Variable-At-A-Time) in a Completely Randomized Design, including particle sizes (20–100 mesh), carapace-to-alcalase ratios (1:1 up to 1:5 w/v), and hydrolysis times (10–180 min). The steam-explosion pretreatment was carried out by heating carapace powder in a steam-explosion at 130–140 ºC for 3 min. Subsequently, astaxanthin was extracted using a sonicator with acetone 1:7 (w/v) at 50 ºC for 20 min. The best alcalase pretreatment results were obtained with a particle size of 80–100 mesh, carapace-to-alcalase ratio of 1:2 (w/v), and a hydrolysis time of 40 min, which increased the relative astaxanthin yield by 23.69% and had no significantly effect on IC50 compared to the control (unpretreated carapace). The steam-explosion pretreatment decreased the relative astaxanthin yield by 63.89%, but increased on IC50 by a factor of 2 compared with the control (indicating increased antioxidant activity). HPLC chromatograms showed that the main component of all extracts was trans-astaxanthin. The results suggest that alcalase pretreatment is a potential to increase the yield, whereas steam-explosion pretreatment is a potential to increase the antioxidant activity of astaxanthin extracted. The development of astaxanthin recovery technology and the utilization of carapace waste can support a sustainable blue economy.